2008
DOI: 10.1103/physrevlett.101.016404
|View full text |Cite
|
Sign up to set email alerts
|

Crystal-Field Level Inversion in Lightly Mn-DopedSr3Ru2O7

Abstract: Sr3(Ru(1-x)Mnx)2O7, in which 4d-Ru is substituted by the more localized 3d-Mn, is studied by x-ray dichroism and spin-resolved density functional theory. We find that Mn impurities do not exhibit the same 4+ valence of Ru, but act as 3+ acceptors; the extra eg electron occupies the in-plane 3d(x2-y2) orbital instead of the expected out-of-plane 3d(3z2-r2). We propose that the 3d-4d interplay, via the ligand oxygen orbitals, is responsible for this crystal-field level inversion and the material's transition to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 17 publications
3
39
0
Order By: Relevance
“…2H. This is consistent with previous assessment that the high temperature metal and the low temperature insulator in Sr 3 ðRu 1−x Mn x Þ 2 O 7 correspond to PM and AFM phases respectively (16,17), although the MIT occurs at much higher temperature than that of magnetic ordering.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…2H. This is consistent with previous assessment that the high temperature metal and the low temperature insulator in Sr 3 ðRu 1−x Mn x Þ 2 O 7 correspond to PM and AFM phases respectively (16,17), although the MIT occurs at much higher temperature than that of magnetic ordering.…”
Section: Resultssupporting
confidence: 80%
“…The substitution of Ru by Mn strengthens the electron correlation via the modification of the lattice, and the system becomes a Mott insulator at low temperatures (16). According to previous work (16,17) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Is band filling also changed? According to XAS data, Mn acts as 3+ in Sr 3 (Ru 0.9 Mn 0.1 ) 2 O 7 [13]. If this were the case, one would expect (1) expansion of the lattice unit cell as Mn 3+ (0.65Å) has large ionic radius than Ru 4+ (0.62Å), (2) effective S ∼2 for high spin (HS) state or S =1 for intermediate spin (IS) state, (3) Ru would exhibit 5+ valence, or (4) oxygen deficiency while Ru remains 4+.…”
Section: Single Crystals Of Srmentioning
confidence: 99%
“…X-ray absorption spectroscopy (XAS) indicated that the Mn dopant has an oxidation state different from Ru 4+ [13], while x-ray photoemission spectroscopy (XPS) showed no sign of dopinginduced multiple Ru valences up to x =0.2 [14]. We have studied Sr 3 (Ru 1−x Mn x ) 2 O 7 over an extended doping range with 0≤x ≤0.7.…”
mentioning
confidence: 93%